Crowding out vs. crowding in effects in transitional countries - Maric, Zeljko (Perspectives of Innovations, Economics and Business, 2015)
In general, transitional countries have the higher level of factor of production unemployment, significantly under the level of full employment. According to the economic theory and historical experiences of today developed countries, the appropriate economic policy for transitional countries should be Keynesianism, where the fiscal policy, i.e. public expenditure policy has the key role. The public expenditure efficiency, as the instrument of economic policy is determined by two effects: crowding out and crowding in effects. If the public expenditure has the positive influence on private expenditure (personal expenditure and private investments), it is the case of crowding in effect. But, if the public expenditure has negative influence on private expenditure, it is the case of crowding out effect. The subject of this paper is the analysis of the determinants of public expenditure effects in the case of transitional countries. The paper gives the theoretical analysis of crowding out and crowding in effects which depend of public expenditure structure, sources of financing and existing economic situation. After that, it will be explained by the empirical analysis of possible public expenditure effects in electric-power system in Bosnia and Herzegovina.